Increased Pain Symptomatology Among Females vs. Males With Fragile X-Associated Tremor/Ataxia Syndrome - Johnson, Devon; Santos, Ellery; Kim, Kyoungmi; Ponzini, Matthew D.; McLennan, Yingratana A.; Schneider, Andrea; Tassone, Flora; Hagerman, Randi J. (Frontiers in Psychiatry, 2022)
Individuals with the fragile X premutation report symptoms of chronic pain from multiple systems, have increased incidence of comorbid conditions where pain is a prominent feature, and pathophysiology that supports disrupted pain regulation, inflammation, and energy imbalance. Less is known about how pain manifests for the subpopulation of carriers that develop the motor and cognitive changes of Fragile X-associated Tremor and Ataxia Syndrome (FXTAS), and how pain may differ between men and women. We gathered data collected from 104 males and females with FXTAS related to chronic pain, comorbid conditions related to pain, and medications used for pain control to further explore the types of pain experienced and to better characterize how individuals with the fragile X premutation experience pain sensation across genders. We found that women experience significantly more pain symptoms than men, particularly allodynia (20% vs. 2.0%, p=0.008), peripheral neuropathy pain (43.9% vs. 25.4%, p=0.0488), migraines (43.9% vs. 14.5%, p=0.0008), fibromyalgia (26.8% vs. 0%, p=0.0071) and back pain (48.5% vs. 23.4%, p=0.008). We found onset of peripheral neuropathy predicts the onset of ataxia (β=0.63±0.25, p=0.019) and tremor (β= 0.56±0.17, p=0.004) across gender. Women also report significant more anxiety (82.9% vs. 39.7%, p<0.001), which has implications for ideal pain treatment. These pain symptoms need to be recognized in the medical history and treated appropriately, with consideration for overlapping comorbidities.